Características epidemiológicas, clínicas y quirúrgicas de la apendicitis en la población pediátrica del Hospital Belén de Trujillo - Montes Baltodano, Carlos Enrique (2016)
Objective: To determine the clinical and epidemiological characteristics of appendicitis in the pediatric population of Trujillo Belen Hospital. Material and Methods: A descriptive, retrospective, observational study was carried out. The study population consisted of 195 pediatric patients with acute appendicitis. The characteristics corresponding to the clinical and epidemiological profile of the patients were identified. Results: Distribution of children with acute appendicitis according to age was: 0 to 3 years (9%); 4 to 6 years (14%); 7 to 9 years (21%); 10 to 12 years (25%); 13 to 15 years (31%); According to sex was: male (55%) and female (45%); According to disease time was <12 hours (57%); 12 to 24 hours (35%) and> 24 hours (8%); Nausea or vomiting (87%) and nausea or vomiting (13%); According to Mc Burney's sign was positive (95%) and negative (5%); According to Blumberg's sign was positive (73%) and negative (27%); According to Rowsing's sign was positive (56%) and negative (44%); According to hospital stay was: less than 3 days (37%) from 3 to 5 days (46%) and greater than 5 days (13%); according to mortality results were: Positive (0%) and negative (100%); according to anatomapathological diagnostic results were: congestive appendicitis (9%), suppurative appendicitis (39%), gangrenous appendicitis (20%), perforated appendicitis (32%); The most common post-operative complication was wound infection (6%); conventional surgery predominated (96%). Conclusions: The clinical and epidemiological characteristics of appendicitis in the pediatric population of Trujillo Belen Hospital are similar to those described in other populations